Закордонний досвід трансформацій національних економік та можливість його застосування в Україні в умовах загострення системної кризи - Гармаш, Сергій Володимирович (НТУ "ХПІ", 2015)
У статті аналізується можливість застосування іноземного досвіду трансформування національної економіки в результаті проведення радикальних реформ у контексті розвитку українського суспільства в цілому в умовах загострення системної кризи. Розкривається сутність реформ «шокової терапії» Л. Бальцеровича у Польщі, проводиться порівняльний аналіз та робиться висновок щодо доцільності впровадження таких реформ в Україні у сучасних умовах.

Possible using of foreign experience of national economy transformation in the course of carrying out of radical reforms in the context of Ukrainian society development in the whole in conditions of systemic crisis intensification is examined in this paper. The main point of Bal’tserovich’s reforms of «shock therapy» in Poland and obvious progress as the result of such reforms are analysed; comparative analysis of situations is carried out; conclusion dealing with the suitability of adoption such reforms in Ukraine under present-day conditions is deduced.
Foreign experience of national economies transformation and its possible using in Ukraine in conditions of systemic crisis intensification
Keywords: радикальні реформи; шокова терапія; суспільство; radical reforms; national economy transformation; systemic crisis